Buparlisib is a novel inhibitor of daunorubicin reduction mediated by aldo-keto reductase 1C3 - Bukum, Neslihan; Novotna, Eva; Morell, Anselm; Hofman, Jakub; Wsol, Vladimir (Chemico-biological interactions, 2019)
Buparlisib is a pan-class I phosphoinositide 3-kinase (PI3K) inhibitor and is currently under clinical evaluation for the treatment of different cancers. Because PI3K signalling is related to cell proliferation and resistance to chemotherapy, new therapeutic approaches are focused on combining PI3K inhibitors with other anti-cancer therapeutics. Carbonyl-reducing enzymes catalyse metabolic detoxification of anthracyclines and reduce their cytotoxicity. In the present work, the effects of buparlisib were tested on six human recombinant carbonyl-reducing enzymes: AKR1A1, AKR1B1, AKR1B10, AKR1C3, and AKR7A2 from the aldo-keto reductase superfamily and CBR1 from the short-chain dehydrogenase/reductase superfamily, all of which participate in the metabolism of daunorubicin. Buparlisib exhibited the strongest inhibitory effect on recombinant AKR1C3, with a half-maximal inhibitory concentration (IC50) of 9.5 μM. Its inhibition constant Ki was found to be 14.0 μM, and the inhibition data best fitted a mixed-type mode with α = 0.6. The same extent of inhibition was observed at the cellular level in the human colorectal carcinoma HCT 116 cell line transfected with a plasmid encoding the AKR1C3 transcript (IC50 = 7.9 μM). Furthermore, we performed an analysis of flexible docking between buparlisib and AKR1C3 and found that buparlisib probably occupies a part of the binding site for a cofactor most likely via the trifluoromethyl group of buparlisib interacting with catalytic residue Tyr55. In conclusion, our results show a novel PI3K-independent effect of buparlisib that may improve therapeutic efficacy and safety of daunorubicin by preventing its metabolism by AKR1C3.
Keywords: Inhibitory Concentration 50; Cancer; Catalytic Domain; Multidrug resistance; Morpholines; morfoliny; Anthracyclines; HCT116 buňky; Humans; simulace molekulového dockingu; Daunorubicin; Aldo-Keto Reductases; Aminopyridines; Molecular Docking Simulation; HCT116 cell line; inhibiční koncentrace 50; aldo-keto reduktasy; Aldo-Keto Reductase Family 1 Member C3; vazebná místa; lidé; Recombinant Proteins; Buparlisib; Binding Sites; daunomycin; protein AKR1C3; rekombinantní proteiny; Kinetics; katalytická doména; AKR1C3; aminopyridiny; HCT116 Cells; kinetika